2021
DOI: 10.1186/s40814-021-00836-w
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin for uncomplicated severe acute malnutrition: study protocol for a pilot randomized controlled trial

Abstract: Background Given the high risk of infectious mortality among children with severe acute malnutrition (SAM), the World Health Organization recommends routine administration of a broad-spectrum antibiotic like amoxicillin as part of the management of uncomplicated SAM. However, evidence for the efficacy of amoxicillin to improve nutritional recovery or reduce mortality has been mixed. With a long half-life and evidence of efficacy to reduce mortality in high-risk populations, azithromycin is a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…[31][32][33] A pilot trial in Burkina Faso testing the efficacy of azithromycin to improve nutritional outcomes in children with uncomplicated severe acute malnutrition has recently completed recruitment. 34 With regard to secondary outcomes, the difference in the composite outcome of hospitalization or death merits consideration. There was a 21% lower risk of hospitalization or death in the 90-day follow-up period in the azithromycin group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] A pilot trial in Burkina Faso testing the efficacy of azithromycin to improve nutritional outcomes in children with uncomplicated severe acute malnutrition has recently completed recruitment. 34 With regard to secondary outcomes, the difference in the composite outcome of hospitalization or death merits consideration. There was a 21% lower risk of hospitalization or death in the 90-day follow-up period in the azithromycin group.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 , 33 A pilot trial in Burkina Faso testing the efficacy of azithromycin to improve nutritional outcomes in children with uncomplicated severe acute malnutrition has recently completed recruitment. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Complete methods for the trial have been previously reported (O'Brien, Sié, Dah, Ourohire, Arzika, et al, 2021;O'Brien, Sie, Dah, Ourohire, Ouédraogo, et al, 2021) Participants were recruited via outpatient nutritional programmes at six primary health care facilities in Boromo District, Burkina Faso from June through October 2020.…”
Section: Study Settingmentioning
confidence: 99%
“…Response to treatment for outpatient SAM may be different for children admitted based on different criteria given that these criteria identify different subpopulations of children. We utilized data from a randomized controlled trial of azithromycin compared with amoxicillin for outpatient management of SAM (O'Brien, Sié, Dah, Ourohire, Arzika, et al, 2021 ) to evaluate response to treatment in children admitted to outpatient nutritional programmes based on low MUAC, low WHZ, or low MUAC and WHZ. We further evaluated outcomes in children with low WAZ and height‐for‐age Z ‐score (HAZ) at enrolment, as these markers may be useful in identifying the highest‐risk children who may benefit from admission to a nutritional programme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation